Further understanding the premixed methane/hydrogen/air combustion by global reaction pathway analysis and sensitivity analysis. (1st January 2020) - Wang, Du; Ji, Changwei; Wang, Shuofeng; Meng, Hao; Wang, Zhe; Yang, Jinxin
Abstract: In this study, the laminar premixed CH4 /H2 /air combustion was investigated by the global reaction pathway (GP) analysis and sensitivity analysis of physical parameters for individual species under various hydrogen fractions ( α ) and pressures to further understand the blended fuel combustion and explore two questions: (1) whether extra GPs exist in the blended fuel combustion beyond the pure fuel reacting system; (2) whether there are insignificant species in pure CH4 and H2 combustion showing large influence in binary fuel combustion. Results show that different GPs dominate fuel oxidation under different α . The increasing radicals are responsible for the linearly increasing laminar burning velocity (LBV) at small α, and the transition from CH4 chemistry to H2 chemistry is responsible for the nonlinearly increasing LBV at large α . Extra GPs are shown and play a role in the binary fuel combustion, but they are still within the CH4 chemistry. For most species, the sensitivity of transport and thermal parameters to laminar burning velocity were found has a positive relationship with their maximum mole fraction at different α. No species were found only important to the binary fuel, however, some species such as H2 O show higher sensitivity for binary fuel combustion than that of pure fuel combustion. The changes of GPs with increasing pressure verifies that CH4 chemistry is dominant for small α (20%) combustion while H2 chemistry dominant is for large α (80%) combustion. Most physical parameter sensitivity will increase with increasing combustion pressure, which should be paid more attention in high-pressure combustion.